How do students’ digital financial literacy and financial confidence influence their financial behavior and financial well-being? - Respati, Dwi Kismayanti; Widyastuti, Umi; Nuryati, Tutty; Musyaffi, Ayatulloh Michael; Handayani, Bestari Dwi; Ali, Najmatu Rahma (Nurture, 2023)
Purpose: An understanding of financial literacy is important not only for business actors but also for individuals and households; even there is a need to introduce this all-important skill to children early. There is a projection that the financial behavior of the young generation will have a better influence on the global economy than that of the previous generation. Therefore, it is crucial that today’s young generation understands financial literacy. This study aims to measure how digital financial literacy and financial confidence can influence both the financial behavior and financial well-being of the younger generation. Design/methodology/approach: The participants in this study are university students from all over Indonesia. This is a quantitative research project that uses online questionnaires, and the collected data is processed using structural equations mode-partial least squares (SEM-PLS) with the Smart-PLS application. Questionnaires have been distributed and obtained by 353 respondents to be processed by the Smart-PLS application. Finding: The result indicates that digital financial literacy has a significant effect on financial behavior, and financial behavior also has a significant effect on financial well-being. Meanwhile, financial confidence influences both financial well-being and financial behavior. Conclusion: This research contributes to the body of knowledge by providing information to the public about the importance of digital financial literacy for individuals to control their financial behaviour amidst the rapid growth of financial technology. Furthermore, the research findings are enriched with literature on digital financial literacy, which is still rarely studied. However, a limitation of this study is the fact that the respondents are mainly women. Therefore, there should be further research involving a higher number of respondents and covering a wider research location.